Psychological aspects of diabetes care: effecting behavioral change in patients - Chew, Boon How; Shariff Ghazali, Sazlina; Fernandez, Aaron (Baishideng Publishing Group, 2014)
Patients with diabetes mellitus (DM) need psychological support throughout their life span from the time of diagnosis. The psychological make-up of the patients with DM play a central role in self-management behaviors. Without patient’s adherence to the effective therapies, there would be persistent sub-optimal control of diseases, increase diabetes-related complications, causing deterioration in quality of life, resulting in increased healthcare utilization and burden on healthcare systems. However, provision of psychosocial support is generally inadequate due to its challenging nature of needs and demands on the healthcare systems. This review article examines patient’s psychological aspects in general, elaborates in particular about emotion effects on health, and emotion in relation to other psychological domains such as cognition, self-regulation, self-efficacy and behavior. Some descriptions are also provided on willpower, resilience, illness perception and proactive coping in relating execution of new behaviors, coping with future-oriented thinking and influences of illness perception on health-related behaviors. These psychological aspects are further discussed in relation to DM and interventions for patients with DM. Equipped with the understanding of the pertinent nature of psychology in patients with DM; and knowing the links between the psychological disorders, inflammation and cardiovascular outcomes would hopefully encourages healthcare professionals in giving due attention to the psychological needs of patients with DM.